Clickable azide-functionalized bromoarylaldehydes – synthesis and photophysical characterization - Göbel, Dominik; Friedrich, Marius; Lork, Enno; Nachtsheim, Boris J. (Beilstein Journal of Organic Chemistry, 2020)
Herein, we present a facile synthesis of three azide-functionalized fluorophores and their covalent attachment as triazoles in Huisgen-type cycloadditions with model alkynes. Besides two ortho- and para-bromo-substituted benzaldehydes, the azide functionalization of a fluorene-based structure will be presented. The copper(I)-catalyzed azide–alkyne cycloaddition (CuAAC) of the so-synthesized azide-functionalized bromocarbaldehydes with terminal alkynes, exhibiting different degrees of steric demand, was performed in high efficiency. Finally, we investigated the photophysical properties of the azide-functionalized arenes and their covalently linked triazole derivatives to gain deeper insight towards the effect of these covalent linkers on the emission behavior.
Keywords: bromoarylaldehydes; click-chemistry; fluorenes; fluorescence; phosphorescence